Minimum wage, poverty and vulnerable social class, a case study in Ecuador - Herrero-Olarte, Susana; Bustamante-Sage, Francisca (Iberoamerican Journal of Development Studies, 2025)
The increase in the minimum wage in South American countries can follow frameworks and guides, amongst other factors, from those defined in Anglo-Saxon countries. For neoliberalism, minimum wages and poverty have a positive relationship, while for post-Keynesianism it is negative. In this research, we identify the variations of the minimum wage have on the incomes of the different economic deciles in Ecuador. We conclude that the variation of the minimum wage does not impact the decline in «extreme poverty», decile 1. It impacts the decile closest to the minimum wage, decile 4, but also deciles 2, 3 and 5, because there is a «lighthouse effect» on them. Increasing the minimum wage can be an effective policy to reduce poverty and sustain the vulnerable social class (those between poverty and the middle class). Reducing informality would make the impact of the minimum wage more transparent, which would improve its capacity as a public policy tool.